Typologia miejskich srebrnych singli w wybranych miastach w Polsce - Tomasz Zalega (Studia i Materiały)
Purpose: The article presents the results of empirical research on the typology of urban silversingles’ households in Poland. The study concerned the financial situation, structure of expenditure, home infrastructure, consumer behaviour, and selected consumer trends such as sustainable consumption, smart shopping, cocooning, consumption virtualization, and consumer ethnocentrism.